Dealers' incentives to reveal their names. Issue 1 (13th April 2020) - Karam, Arzé
Abstract: This research investigates dealers' motivation to disclose their names when quoting on the NASDAQ over the years. NASDAQ enables dealers to quote limit orders either anonymously or with a feature that reveals their names. Results are consistent with dealers advertising by revealing their identities so as to develop and maintain their reputation for reliable pricing. Dealers strategically choose to reveal their identities when order flow is profitable. Post‐name disclosure analysis further suggests that named quotations are likely to be driven by informational considerations. This research contributes to our understanding of the use of non‐anonymity in electronic trading.